Carga interna, tolerância ao estresse e infecções do trato respiratório superior em atletas de basquetebol - Gobo Freitas, G.; Saldanha Aoki, M.; Schultz Arruda, A. F.; Nakamura, F. Y.; Moreira, A. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
The present study aimed to investigate the effect of external training load manipulation on internal training load (ITL), stress tolerance (ST) and upper respiratory tract infection (URTI) severity in basketball players during a 19-week macrocycle. The macrocycle was divided into three distinct phases: preparatory phase (P1) and two competitive phases (P2 and P3). The Daily Analysis of Life Demands for Athletes questionnaire (DALDA), for assessment of sources and symptoms of stress, and the Wisconsin Upper Respiratory Symptom Survey (WURSS-21), for evaluation of URTI severity, were used on a weekly basis. The ITL was assessed by Rating of Perceived Exertion (session RPE). There was a decrease in ITL at P3 when compared to P1 and P2 (p < 0.05). A decrease in "better than normal" responses in DALDA for both sources and symptoms of stress was observed at P2 and P3 when compared to P1 (p < 0.05). There was also a significant increase in URTI severity. In addition, significant relationships between ST and URTI were shown at P3, suggesting that stress tolerance may modulate URTI severity. In summary, ETL manipulation induced changes in ITL. However, unlike the initial hypothesis, a decrease in ITL during the competitive period was followed by a decrease in stress tolerance and an increase in URTI severity. Furthermore, the magnitude of stress seems to provoke an increase in URTI severity.